Kulturtransfer und Wissenszirkulation in den langen 1960er Jahren Das deutsch-amerikanische Fulbright-Programm für Lehrer:innen - Wedde, Sarah (Studien zur Deutsch-Amerikanischen Bildungsgeschichte / Studies in German-American Educational History, 2023)
Cultural Transfer and Circulation of Knowledge in the long 1960s. The German-American Fulbright Program for teachers. The dissertation traces intercultural knowledge movements between West Germany and the United States in the long 1960s, initiated by the teacher exchange of the German-American Fulbright Program, focussing on everyday culture and the educational/professional context. For the first time, the Annual Exchange Teacher's Reports on Teaching Experiences in the United States, which are kept in the archives of the German-American Fulbright Commission in Berlin, will be evaluated alongside further sources on the institutionalization, design and operationalization of the German-American Fulbright Program. The reports were submitted as completed questionnaires and form the basis of the work as a serial source. They provide information on how German exchange teachers perceived and reflected on their stay in the USA and show which misconceptions were consolidated or overcome. At the same time, knowledge circulation can be traced, and exchange teachers can be identified as agents of a knowledge movement after World War II. The aim here is not so much to write a normative success story of a straightforward US culture transfer to West Germany. Rather, the focus is on the multi-layered, interwoven, and above all open-ended knowledge movements as part of the German-American educational and cultural transfer processes of the post-war period. The focus will be on the agents, networks, structures, and communication spaces within the German-American Fulbright Program in order to understand where, how, and by whom elements were reflected, selected, adapted, and reshaped or rejected. Thus, the transatlantic exchange encounters of Fulbright teachers indicate that cultural objects and patterns of action as well as societal values were adopted from the United States, thus creating a readiness for modernization through adaptations and reinterpretations. The Fulbright Program continued the German-American educational exchange, setting new accents which influenced developments in the Federal Republic of Germany after 1945, especially in education and everyday culture, while at the same time aiding German culture in its initial opening up to ,Americanization'. As a result, the exchange teachers contributed to the cultural transfer between the U.S. and the Federal Republic of Germany in the long 1960s.